2012
DOI: 10.1109/te.2011.2175227
|View full text |Cite
|
Sign up to set email alerts
|

Pipelined CPU Design With FPGA in Teaching Computer Architecture

Abstract: This paper presents a pipelined CPU design project with a field programmable gate array (FPGA) system in a computer architecture course. The class project is a five-stage pipelined 32-bit MIPS design with experiments on the Altera DE2 board. For proper scheduling, milestones were set every one or two weeks to help students complete the project on time. The goal of the project is to educate students effectively via hands-on learning, rather than having them achieve a complete and flawless CPU design. This study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 14 publications
1
16
0
Order By: Relevance
“…Additionally, students indicated that the intended course objectives were accomplished and that there was a good level of satisfaction. These opinions are similar to those obtained by other similar studies demonstrating the effectiveness of FPGA-based systems in engineering courses [39][40][41][42].…”
Section: Discussionsupporting
confidence: 90%
“…Additionally, students indicated that the intended course objectives were accomplished and that there was a good level of satisfaction. These opinions are similar to those obtained by other similar studies demonstrating the effectiveness of FPGA-based systems in engineering courses [39][40][41][42].…”
Section: Discussionsupporting
confidence: 90%
“…Pipelining does not reduce the total time taken by an instruction, but it increases the number of instruction that can be processed at once, and instruction throughput is increased. Even though pipelining introduces latency in the output, the maximum frequency of operation is increased (Lee, Lee, Yu, & Suh, 2012).…”
Section: Related Workmentioning
confidence: 99%
“…So some teachers propose to enforce active hands-on practices by utilizing the reconfigurable hardware platforms [11,12,13,14].…”
Section: Introductionmentioning
confidence: 99%